2021
DOI: 10.3389/fnagi.2021.721474
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 Inflammasome-Dependent Increases in High Mobility Group Box 1 Involved in the Cognitive Dysfunction Caused by Tau-Overexpression

Abstract: Tau hyperphosphorylation is a characteristic alteration present in a range of neurological conditions, such as traumatic brain injury (TBI) and neurodegenerative diseases. Treatments targeting high-mobility group box protein 1 (HMGB1) induce neuroprotective effects in these neuropathologic conditions. However, little is known about the interactions between hyperphosphorylated tau and HMGB1 in neuroinflammation. We established a model of TBI with controlled cortical impacts (CCIs) and a tau hyperphosphorylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Innate immune signaling through the NLRP3 inflammasome has been implicated in the pathogenesis of AD [5][6][7][8][9][10][11][12][13] . A therapy that inhibits inflammasome activation could thus be neuroprotective and improve clinical outcomes in AD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Innate immune signaling through the NLRP3 inflammasome has been implicated in the pathogenesis of AD [5][6][7][8][9][10][11][12][13] . A therapy that inhibits inflammasome activation could thus be neuroprotective and improve clinical outcomes in AD.…”
Section: Discussionmentioning
confidence: 99%
“…; https://doi.org/10.1101/2023.03.17.23287375 doi: medRxiv preprint 4 NLRP3 inflammasome, a multimeric protein complex that responds to aberrant Aβ and tau aggregation by launching a potent inflammatory response characterized by caspase-1 activation, interleukin-1β (IL-1β) release, and neuronal cell death [5][6][7][8] . In turn, NLRP3 activation facilitates further deposition of Aβ plaques and tau fibrils, establishing a positive feedback loop that contributes to the development of AD [9][10][11][12][13] . NLRP3 inflammasome inhibition may protect against AD progression 9,14 .…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…Tau pathology has a direct positive correlation with neuroinflammation in the parahippocampus of AD patients examined by positron emission tomography [ 42 ]. Hyperphosphorylated tau trigger neuroinflammation in an NLRP3-dependent manner to activate IL-1β levels and impair spatial memory [ 43 ]. In this study, we found that Aβ 25–35 could promote the release of proinflammatory cytokines, and W112 prevented the over-production of TNF-α and IL-6 both in vitro and in vivo studies.…”
Section: Discussionmentioning
confidence: 99%
“…Panda et al used tau-derived PHF6 peptide (VQIVYK) to stimulate microglia and found that VQIVYK in the form of fibrous aggregates upregulated the expression of NLRP3 at mRNA and protein levels in a dose- and time-dependent manner, ultimately leading to increased expression of IL-1β and IL-18 ( Panda et al, 2021 ). Experimental results from in vivo also show that hyperphosphorylation of tau in the mouse brain significantly increases the activation of NLRP3 inflammasome and the up-regulation of IL-1β levels ( Zhao et al, 2021 ). In summary, we speculate that the role of tau in NLRP3 inflammasome is similar to Aβ.…”
Section: The Role Of Nlrp3 Inflammasome In Alzheimer’s Diseasementioning
confidence: 99%